The Impact of Palestinian Literature and Cinema on Indonesian Cultural Understanding of the Middle East Conflict (Palestine Issues on Indonesian Society, 2024)
This paper explores how Palestinian literature, films, and other cultural productions have shaped the Indonesian public’s understanding of the Palestinian struggle and the broader Middle Eastern political context. The study examines key works of Palestinian authors, filmmakers, and artists that have been translated and disseminated in Indonesia, and assesses their impact on Indonesian cultural consciousness. By analyzing the reception of these cultural products, the paper investigates how they provide an alternative narrative to mainstream Western media portrayals of the conflict, offering a more nuanced and humanistic view of Palestine. The paper also explores how these cultural representations intersect with Indonesia’s own political history and identity, particularly in terms of solidarity with oppressed peoples and anti-colonial movements. Through this cultural lens, the study highlights the role of literature and cinema as tools for building cross-cultural understanding and political empathy in Indonesian society.